Cambodia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
Contents include--The real economy: background and recent developments; public finance; fiscal developments during 1994-95 and budgetary policy in 1996; Money and banking; structure of the banking system;monetary policy instruments; monetary developments; and issues in banking supervision; the external sector; recent developments; external financial assistance; external debt; trade regimel; customs operations; and exchange system;the changing role of the state; enterprise reform; privatization; and foreign direct investment; forestry sector and forestry policy;trends and developments; recent concession policy; and a sustainable new forestry policy; statistical tables.